Invariant mass distribution of jet pairs produced in association with a W boson in pp collisions at sqrt[s]=1.96 TeV. - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2011)
We report a study of the invariant mass distribution of jet pairs produced in association with a W boson using data collected with the CDF detector which correspond to an integrated luminosity of 4.3  fb(-1). The observed distribution has an excess in the 120-160  GeV/c(2) mass range which is not described by current theoretical predictions within the statistical and systematic uncertainties. In this Letter, we report studies of the properties of this excess.